Perancangan dan Implementasi Back end Website Profile & Crud Product Knowledge di PT. Panca Utama - Lius, Kevin; Sama, Hendi; Yulianto, Andik (National Conference for Community Service Project (NaCosPro), 2025)
This community service activity aims to design and implement a backend system for a corporate profile website and product knowledge CRUD features for PT. Panca Utama. The company, which supplies equipment to the hospitality industry, previously lacked a digital platform to support its online presence and customer engagement. The development process followed the Scrum framework, consisting of sprint planning, collaborative development, iterative evaluation, and implementation phases. Django, a Python-based backend framework, was employed to build a secure, structured, and efficient system. The final website successfully fulfilled the partner's needs in terms of functionality, accessibility, and ease of content management. The implementation contributed to improving the company’s digital visibility and enhancing customer service quality. Beyond the direct benefits to the partner, this program also provided students with practical experience in applying technical skills in a real-world industrial context.